simplify: (x^2-8x+16)/(x^2-x-12)÷(4x-x^2)/(2x)

### 1 Answer | Add Yours

We have to simplify: (x^2-8x+16)/(x^2-x-12)÷(4x-x^2)/(2x)

Now, x^2 - 8x + 16 = (x - 4)^2

x^2 - x - 12 = x^2 - 4x + 3x - 12

=> x(x - 4) + 3(x - 4) = (x + 3)(x - 4)

4x - x^2 = x(4 - x)

[(x^2-8x+16)/(x^2-x-12)]/[(4x-x^2)/(2x)]

=> [(x - 4)^2/(x + 3)(x - 4)]/[x(4 - x)/2x]

=> [(x - 4)/(x + 3)]/[(4 - x)/2]

=> 2(x - 4) / (x + 3)(4 - x)

=> -2/ (x + 3)

**The simplified form is -2/ (x + 3)**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes